ChemInform Abstract: Synthesis and Antiproliferative Studies of 5‐Aryl‐2‐(3‐thienylamino)‐1, 3, 4‐thiadiazoles. Issue 41 (7th October 2014) - Revelant, Germain; Gadais, Charlene; Mathieu, Veronique; Kirsch, Gilbert; Hesse, Stephanie
Abstract A wide range of the title compounds (IV) are formed in good yields in two steps starting from thiophen‐3‐isothiocyanates.